Alcohol Use Severity Among Hispanic Emerging Adults in Higher Education: Understanding the Effect of Cultural Congruity. (19th September 2015) - Cano, Miguel Ángel; Vaughan, Ellen L.; de Dios, Marcel A.; Castro, Yessenia; Roncancio, Angelica M.; Ojeda, Lizette
Abstract : Background: Identifying and understanding determinants of alcohol use behavior among Hispanic college students is an increasingly important public health issue, particularly during emerging adulthood. Studies examining ethnocultural determinants of alcohol use behavior among Hispanic college students have focused on direct associations with cultural orientation (e.g., acculturation and enculturation); yet there is a need for research that accounts for the complex interplay of other culturally relevant sociocultural factors. Objectives: This study examined associations of behavioral acculturation, behavioral enculturation, and cultural congruity (perception of cultural fit between the values of the academic environment and the student's personal values) with alcohol use severity (AUS); and tested if gender moderated those associations. Methods: A hierarchical linear regression and moderation analysis were conducted on a sample of 167 Hispanic emerging adults (ages 18–25) enrolled in college. Results: All predictor variables entered in the regression model accounted for 20.9% of the variance in AUS. After controlling for demographic variables and depressive symptoms, behavioral acculturation and enculturation did not have a statistically significant association with AUS. Further, gender did not moderate either of these associations. Conversely, greater cultural congruity was associated with lower reports of AUS. A moderation analysis suggested that cultural congruity predicted lower reports of AUS among men, but not among women. Conclusions: This was the first known study to examine the association of cultural congruity with alcohol use. Findings highlight the value of examining contextual factors of culture and moving beyond reductive measures of cultural orientation.